Wednesday

July 23, 2014

July 23, 2014

Posted by **Mike** on Tuesday, May 29, 2007 at 12:33pm.

5/(y-2)=y+2

(x/3)-(2/3)=(1/y-5)

(y+2)/7=1(y-5)

(x^2)/(x-4)-7/(x-4)=0

x^2/(x+3)-5/(x+3)=0

I assume that your second equation has y as a typo. I will use that as an example.

(x/3)-(2/3)=(1/x-5)

Multiply both sides by 3. I will also assume that (1/x-5) is the same as (1/x)-5 rather than 1/(x-5).

x-2=3/x-15

Get the x terms on one side and the numerical terms on the other by adding 2 and subtracting 3/x from both sides.

x-3/x=17

Multiply both sides by x.

x^2-3=17x

x^2-17x-3=0

Unfortunately, I cannot carry the process further. However, it should make the process clear.

I hope this helps. Thanks for asking.

**Related Questions**

Solving Equations with Rational Expressions - Can someone correct me if I ...

Adding and Subtracting Rational Expressions - Can someone PLEASE show me how to ...

Math - what you have learned about rational expressions and their applications, ...

equations of tangents and normals - hi, i'd really appreciate some help solving ...

Algebra - 40 =15 x x - 20 This is a three part question>> first find the ...

Math - Can someone please help with this problem? Solve by the elimination ...

Algebra2 - Find the polynomials roots to each of the following problems: #1) x^2...

bobpursly & countiblis,math - I thought that we can solve anything with ...

math - Still having problems solving this... 2x(2x + 1)^2 = 312 I started with: ...

Differential Equations - Consider the spring - mass system, shown in Figure 4.2....